Research Synthesis on Community Enterprise Development in Udon Thani Province during 2018 - 2025 - Hemnil, Sunit (Journal of Multidisciplinary Academic Research and Development (JMARD), 2026)
This academic article aims to synthesize research on the development of community enterprises in Udon Thani Province published between 2018 - 2025. The study employed documentary research methods in conjunction with academic synthesis approaches. Research studies were retrieved from online databases of Thai journals and screened for quality according to specified criteria, resulting in 41 research studies selected for this synthesis. The findings indicate that community enterprise operations play a significant role in the community economic system. However, they encounter problems and limitations from both internal and external factors, which have become obstacles to the development of community occupations and income. The research synthesis yielded development approaches for upgrading community enterprises comprising 10 dimensions: 1) products and services, 2) packaging, 3) marketing and sales, 4) accounting and return analysis, 5) human resources and participation, 6) networking, 7) manual and curriculum development, 8) application of Buddhist principles and Sufficiency Economy Philosophy, 9) government certification marks, and 10) distribution center locations and transportation models. Each dimension has generated positive impacts on community enterprise development. However, given that community enterprise operations are complex and overlap across multiple activities, there is a need for development strategies that are systematic, continuous, and linked to multiple sectors. Moreover, adaptation to customer demands and modern market competition is also required.